Moderating Role of Information Asymmetry Between Cognitive Biases and Investment Decisions: A Mediating Effect of Risk Perception - Zhang, Mingming; Nazir, Mian Sajid; Farooqi, Rabia; Ishfaq, Muhammad (Frontiers in Psychology, 2022)
Behavioral Finance is an evolving field that studies how psychological factors affect decision making under uncertainty. This study seeks to find the influence of certain identified behavioral financial biases on the decision-making process of investors in developing countries. This research examines the moderating effect of Information Asymmetry on the two most important and commonly used cognitive biases, namely Anchoring Bias and Optimism Bias and decision making and investigates whether risk perception mediates the relationship between them or not. Quantitative research has been conducted using a structured questionnaire for data collection. After completing the pilot study, a questionnaire was designed and sent to investors via online channels. Data has been collected from 317 real estate investors. Mediation analysis has been performed using model 4 and moderation analysis by applying model 15 of Process Macros (Hayes, 2017) for the interaction effect. The study investigated that both the cognitive biases have a significant positive effect on Property investors' decision-making and risk perception also significantly mediates the relationship between them. Consistency with other studies suggests that Information Asymmetry has a significant moderating effect. The proposed conceptual model provides insight into how investors' decisions are influenced by behavioral Biases in the Property/real estate sector and enhances the understanding of cognitive biases in the Property sector. This study is recommended for real estate investors and policymakers of emerging and developed countries. The current study is the first of its kind, focusing on cognitive biases on property Investment decisions with mediating role of risk perception and the moderating effect of information asymmetry.